Survival Analysis of Sea Turtles Eggs Hatching Success using Cox non Proportional Hazard Regression - Forestryani, Veniola; Fatekurohman, Mohamad; Hadi, Alfian Futuhul (Jurnal ILMU DASAR, 2019)
The aims of this research is to know both the model and also the factors of incubation period and hatching success of eggs of sea turtles in Kuta, Legian and Seminyak Beach, Bali from January to September 2016. The reasearch was conducted by doing survival analysis by using Cox Non Proportional Hazard regression and then compare the model derived from it with log-logistic regression model. Precipitation, location, temperature, humidity, and hours of daylight are the factors which significantly influence incubation period and hatching success of eggs of sea turtles. According to the descriptive analysis, 12≤ precipitaion <18, Seminyak Beach, 28,5≤ temperature <29,5, 86≤ humidity ≤91, and 5,8≤ hours of daylight <8,3 are the factors which have highest percentage of hatching success. Meanwhile 12≤ precipitation <18, Seminyak Beach, 28,5≤ temperature <29,5, 86≤ humidity ≤91, and 0,8≤ hours of daylight <3,3 are the factors which have highest percentage of hatching success based on the hazard value. Although Seminyak Beach has the highest rate of hatching success, it’s not significantly different from Legian beach in respect to the location factor’s categories. Keywords: hatching success, cox non proportional hazard, log-logistic, survival analysis